Incidencia de la Ley 29717 del acto cooperativo en el pago del Impuesto Temporal a los Activos Netos: caso Cooperativa de Ahorro y Crédito San Martín de Porres S.R.L. periodo 2011 - 2012 - García García, Alejandro (2014)
The main purpose of the following research is to explain the incidence of the law 29717 in the cooperative act in the payment of the temporary tax net assets. This is the case of cooperative of savings and credit San Martin de Porres. Periods 2011 and 2012 and it is a relevant specific problem. The hypothesis is as follows: the law 29717 cooperative act has had a favorable impact on the payment of the temporary tax due to the net assets at the cooperative of savings and credit San Martin de Porres SRL. Period 2011-2012. The applied methodology is based on a type of research applied in the explanatory level, with an explanatory transactional no experimental design, using the analytic synthetic method to get sorne data, processing and analysis. The hypothesis is tested in relation to the problem and determine objectives, by applying a survey of union officials at the cooperative the one that allowed to demonstrate the incidence relating their explanatory cause-effect relationship the cooperative act has enabled the successful development of it to not be taxed operations of the cooperative with their partners that relate to its objects and nonprofit reflected in its status.